2014
DOI: 10.2190/ec.51.2.a
|View full text |Cite
|
Sign up to set email alerts
|

Interacting with a Computer-Simulated Pet: Factors Influencing Children's Humane Attitudes and Empathy

Abstract: Previous research by Kaufman (2010a, 2010b) has suggested that computer-simulated virtual pet dogs can be used as a potential medium to enhance children's development of empathy and humane attitudes toward animals. To gain a deeper understanding of how and why interacting with a virtual pet dog might influence children's social and emotional development, this study gathered detailed data regarding the effects of play duration and types of play interaction on the enhancement of children's empathy and humane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several studies have found a link between pet ownership (particularly dogs and cats), pet attachment, positive attitudes to animals, compassion, empathy, and prosocial behaviour [54,55,56,57,58,59]. Humane attitudes and concerns for animal welfare are related to a greater involvement in caring for pets during childhood [60] and similar results have even been found for virtual pets [61]. …”
Section: Introductionmentioning
confidence: 77%
“…Several studies have found a link between pet ownership (particularly dogs and cats), pet attachment, positive attitudes to animals, compassion, empathy, and prosocial behaviour [54,55,56,57,58,59]. Humane attitudes and concerns for animal welfare are related to a greater involvement in caring for pets during childhood [60] and similar results have even been found for virtual pets [61]. …”
Section: Introductionmentioning
confidence: 77%
“…However, despite being outside of the scope of the structured review, some of these studies utilised novel techniques that may be promising for integration into more specific behaviour change intervention trials in the future. For example, Hazel et al [ 27 ] demonstrated that teaching students to clicker-train chickens can improve attitudes towards animals and belief in their cognitive capacities; Helton and Helton [ 28 ] found that presenting information about the cognitive capacities of animals increased ‘pro-animal attitudes’; MacKay et al [ 29 ] used a Massive Open Online Course (MOOC) to reach a very large audience (33,501 people enrolled and 5501 completed the 5 week course); Małecki et al [ 30 ] used literary fiction to improve attitudes towards animals; and Tsai and Kaufman [ 31 ] demonstrated that a virtual pet ‘Nintendogs’ can increase children’s empathy and humane attitudes. What is now needed is for these techniques to be applied to specific behavioural targets and assessed for their ability to change behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies analyzed empathy toward non-human characters like virtual pets. Virtual pets are defined by Tsai (2008) as the simulations of “life-like agents” and could possibly be used to build relationships with players (pp. 49).…”
Section: Introductionmentioning
confidence: 99%
“…49). Tsai and Kaufman (2014, p. 149) used a “real-time pet simulation videogame” called Nintendogs and reported a positive effect of interacting with virtual pets on users’ relationship to pets in real life, suggesting that children playing the game developed an empathic disposition toward the virtual characters. This result supports the conclusion that empathic feelings toward a virtual animal are, in principle, possible.…”
Section: Introductionmentioning
confidence: 99%